Analysis of the influence of asymmetric geological conditions on stability of high arch dam - Ding Zelin (De Gruyter, 2021)
Geological conditions play a decisive role in the stability of arch dam engineering, and the asymmetric geological conditions of the abutment have a very negative impact on the safety of the arch dam. This article takes Lizhou arch dam as the research object, and determines that the arch dam is preliminarily affected by the geological asymmetric characteristics. Through the geomechanical model test method, the overload failure test of the Lizhou arch dam was carried out, and the resistance body, the instability deformation of the structural plane of the two dam abutments, and the influence of each structural plane on the dam body are obtained, and the safety factor is determined. According to the test results under the condition of asymmetric foundation of arch dam, for the structural plane which affects the geological asymmetry of the arch dam, the corresponding reinforcement measures are carried out. The feasibility of the reinforcement scheme is verified by the finite element method, and the safety factor after reinforcement is obtained. According to the results, it is suggested that some engineering measures can be taken to reduce the geological asymmetry between the two banks and ensure the safe and stable operation of the arch dam in the future.